Improving Students’ Speaking Skill By Using Their Spoken Audio Recording In The Middle School - Widyawan, Kristanto Wahyu; Hartati, Elysa ((JELE) Journal Of English Language and Education, 2016)
The background of the study was based on phenomenon at the eighth grade students of SMP Bopkri Godean. Some of them were still too shy or even discourage to speak in English because they did not have enough idea of what to speak. It used their own audio voice recording in teaching English speaking to activate students’ ability in speaking English. So they will have something to speak. It will give positive outcome toward the problem. This was a classroom action research. The object of this study is the eighth class students of SMP Bopkri Godean. The methods of collecting data were using test and observation. The result of this study showed that in the pre cycle, the students’ average score was 41.96. In the first cycle, the students’ average score was 60.93. It means that there was a progress of students’ achievement after being taught by using their spoken audio recording. In the second cycle, the students’ average score was 75.93. Using their audio recording we were able to improve the students’ speaking ability because they became easier to express what they are going to say based on the prompt from us.